Material Planning for Upper Structure Work Based on the Material Requirement Planning (MRP) Method in the Kasih Ibu Hospital Construction Project, Surakarta - Aprilia Regita Tri Cahyani; I Nyoman Dita Pahang Putra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Material inventory in construction projects is something that needs to be managed because it affects the smooth running of a construction project. To overcome this problem, material scheduling was carried out based on the Material Requirement Planning (MRP) method using the Economic Part Period (EPP) lot size technique and the Least Unit Cost (LUC) lot size technique. This research aims to produce material planning processes and results. MRP is a scheduling method to find out the material and quantity of material needed, as well as when the order will be placed. The calculation results obtained using the MRP method are that the EPP lot size requires a total material inventory cost of IDR 20,847,682,834, while the LUC lot size requires an inventory cost of IDR 20,851,272,531. The difference in total costs is IDR 3,589,697 so the EPP lot size is more economical compared to LUC.